Implementation of Land Sale Regulation in Pasuruan District: Pelaksanaan Peraturan Penjualan Tanah di Kabupaten Pasuruan - Pratama , Ilham Muhammad Jalu; Phahlevy , Rifqi Ridlo (Indonesian Journal of Public Policy Review, 2025)
General Background: Land regulation plays a crucial role in ensuring legal certainty over ownership and transfer of land rights in Indonesia. Specific Background: Government Regulation Number 24 of 1997 mandates that every land sale and purchase transaction must be conducted before a Land Deed Official (PPAT) through an authentic deed. However, rural communities in Pasuruan District still practice land transactions using Village Sale and Purchase Statements (SPJB/SKJB), which raises questions about their legal standing. Knowledge Gap: Previous studies have not fully examined the practical coexistence of formal legal frameworks with local customary administrative practices. Aims: This study aims to analyze the implementation of PP No. 24/1997 and assess the legal effectiveness of SPJB/SKJB in land registration processes at the local level. Results: The findings show that several villages continue issuing SPJBs, while the National Land Agency (BPN) only recognizes them if issued before 1997. Novelty: The study reveals persistent local practices that adapt legal frameworks to administrative convenience, reflecting the gap between regulation and social reality. Implications: The research contributes to understanding policy implementation challenges in rural land governance and the need for harmonization between legal norms and community practices. <article class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-turn-id="request-WEB:dcb5dfe7-0c1b-4c66-b50e-93e9de1ac69a-8" data-testid="conversation-turn-6" data-scroll-anchor="false" data-turn="assistant"> <div class="[--thread-content-max-width:40rem] thread-lg:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-1" dir="auto" data-message-author-role="assistant" data-message-id="c94f0263-1658-4464-ac70-58fda177f001" data-message-model-slug="gpt-5"> Highlights: Persistent informal land transaction practices in rural Pasuruan. Limited legal recognition of village-issued sale documents. Need for alignment between state law and community land practices. Keywords: Land Registration, PP 24/1997, Sale and Purchase Deed, PPAT, Village Administration